3D Analysis of Montesinho CFRD using Code-Aster FEM program - Marcelino, J. (2015)
This paper describes the setup of a finite element method (FEM) model for the three dimensional simulation of the construction of a concrete face rockfill dam and filling of the its reservoir using the Code-Aster code. The prototype of the study is the 36.5 m high Montesinho dam, located in the north of Portugal near the Spain border, witch is finishing its construction, at the time of the paper writing. The dam is located in the Sabor river in the Montesinho Natural Reserve and it is a concrete face rockfill dam. Its main purpose is to provide water supply to Bragança town reinforcing the current reserve of the Serra Serrada dam located 3 km west of Montesinho, which is not sufficient to supply Bragança during a normal summer. Due to the fact that the dam is located in Montesinho Natural Reserve, which is a very important and sensitive ecological reserve, very special measures has been taken by the dam owner – ATMAD (Águas de Trás-os- Montes e Alto Douro) to minimize the ecological impacts on the environment. Code-Aster is a general purpose FEM software package, developed by Eléctricité de France (EDF) during many years, for the expertise and the maintenance of EDF's power plants and electrical networks. In 2001 it was decided by EDF to release Code-Aster to the public under the GNU General Public License. Since that it has been under constant development making it more capable do address a wide range of phenomena. Code-Aster is written in Fortran and Python and has more than 1.5 million lines of code. In this study, a finite element procedure was developed to simulate the construction process of the dam and its first filling. To model the behaviour of the rockfill material a elastic model with a simple Drucker-Prager model was used. This is a first approach to further developments. The model parameters were calibrated by large-scale triaxial tests performed on materials used in the dam. The step-by-step construction followed by subsequent impounding of the reservoir was simulated in the numerical procedure. The numerical results agree well with in situ monitoring records of dam settlements, indicating that the three-dimensional finite element procedure applied here can be used to evaluate the deformation of CFRDs.